Interactive effects of soil compaction, biochar application, and soil water regime on the growth, yield, and water use efficiency of upland rice - Adesoyin, A.E.; MacCarthy, D.S.; Adiku, G.S.K. (Scientific African, 2023)
The mechanization of tropical agriculture by conventional tillage has enhanced production and contributed to soil compaction, which has long term adverse effects on soil and crop productivity. Application of biochar is among the several remedial measures proposed to offset the compaction problem. Yet, it is unclear how biochar interacts with varying soil water that occurs under variable weather to mitigate the compaction problem. In this study, a screen house experiment was conducted to investigate the growth, yield, and water use efficiency (WUE) of upland rice (Nerica 14) grown under a range of biochar amended compacted soils and soil water conditions. The experimental design was a com pletely randomized design (CRD) in a factorial arrangement with three bulk density (D) levels (D1= 1.30 Mg m−3, D2 = 1.50 Mg m−3, and D3 = 1.75 Mg m−3), two rates of rice husk biochar (RHB) application: (B) = 0 ton ha−1, and B10 = 10 ton ha−1), and three levels of seasonal irrigation (W1 = 391 mm, W2 = 419 mm, and W3 = 569 mm). Grain yield was influenced by biochar, bulk density and water regime. When averaged across irriga tion levels, the B0 grain yields were 1336 kg ha−1, 947 kg ha−1 and 636 kg ha−1 for D1, D2 and D3, respectively. Biochar application reduced both the runoff, drainage, and improved the crop water use efficiency. In terms of WUE, the treatment combination of B10D1W1 and B10D3W3 recorded the highest (14.27 kg ha−1 mm−1), and least (9.28 kg ha−1 mm−1) values, respectively. Though biochar application improved the WUE under all density lev els, high irrigation (W2, W3) could not compensate for the adverse effect of increasing soil density. It is concluded that the adverse impact of tillage-induced soil compaction on up land rice yield can be effectively alleviated by biochar application under varied soil water conditions.
Research Article
Keywords: bulk density; conventional tillage; plant development